Pengaruh Compression Stockings terhadap Obstructive Sleep Apnea (OSA) Pada Pasien Hemodialisis - Kosasih, Cecep Eli; chania, Astilia; Solehati, Tetti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: Obstructive Sleep Apnea (OSA) in hemodialysis patients results from a shift in the rostral fluid overnight. Compression Stocking is a fairly inexpensive therapy compared to other OSA therapies. Compression Stocking is leg stocking that use a pressure force of 20-30 mmHg, effective in preventing the accumulation of fluid that is installed in accordance with the patient's feet. Objective: to determine the effect of Compression Stockings on Obstructive Sleep Apnea (OSA) hemodialysis patients. Method: Search used several electronic databases such as Google Scholar, Proquest, and PubMed. The inclusion criteria in this literature study were quantitative research papers and experiments in English, full text, peer review, published between 2008-2018. Results: Searching for articles with predetermined keywords obtained 718 articles from the database, Google Schoolar obtained 550 articles, ProQuest obtained 68 articles, and PubMed obtained 100 articles. Articles were screened to 32 articles according to the purpose of the review with inclusion and exclusion criteria. After screening 15 articles that met the criteria were read intensively and then analyzed based on content analysis. Conclusion: An overnight rostral fluid shift is one of the factors contributing to the pathogenesis of OSA in hemodyalysis patients. Compression Stocking can be considered as an alternative therapy to prevent fluid retention in the legs and overnight shift to the neck thus providing evidence for a new therapeutic approach to OSA.